Sentiment analysis and its applications in fighting COVID-19 and infectious diseases: a systematic review - Abdullah Hussein Abdullah Al-Amoodi (Tanjung Malim, 2021)
Sentiment analysis and its applications in fighting COVID-19 and infectious diseases: a systematic review by Abdullah Hussein Abdullah Al-Amoodi